Formal modeling and analysis of timed systems : 14th International Conference, FORMATS 2016, Quebec, QC, Canada, August 24-26, 2016. Proceedings /: 14th International Conference, FORMATS 2016, Quebec, QC, Canada, August 24-26, 2016. Proceedings. (2016) - Unknown
No abstract available